Discolored Components from the Black-streaked Heartwood Extracts of Teak - Ganis Lukmandaru; Tatsuya Ashitani; Koetsu Takahashi (Wood Research Journal, 2021)
With regard to black-streaked discoloration of teak wood, the ethyl acetate extract from successive extraction was examined.  By column chromatography, tectol and and two unknown compounds i.e. C-1 (molecular weight of 240) and C-2 (molecular weight of 210) were isolated. Discoloration tests, i.e. air oxidation, acidic (acetic acid), and alkaline (potassiun hydrogen carbonate) treatments were conducted to the isolated and other standard quinoine compounds (tectoquinone, lapachol, 2-tert-buthyl- anthraqunone, 2-hydroxy-methyl-anthraqunone). The results showed that tectol changes its color by the considerable decreasing in brightness whereas C-1 showed huge decrease in yellowness by air oxydation. Tectol did not change its color in pH value of 2.9 to 8.3 but C-1, C-2, and lapachol did change. Tectoquinone was hardly change color under alkaline or acidic treatment. The difference in quinone coloration might be due the structural features of a hydroxyl group and a double bond conjugated